2021
DOI: 10.4162/nrp.2021.15.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol on the inflammatory response and renal injury in hyperuricemic rats

Abstract: BACKGROUND/OBJECTIVES Hyperuricemic nephropathy is a common cause of acute kidney injury. Resveratrol can ameliorate kidney injury, but the explicit mechanism remains unclear. We investigated the effects of resveratrol on the inflammatory response and renal injury in hyperuricemic rats. MATERIALS/METHODS A rat model of hyperuricemic nephropathy was established by the oral administration of a mixture of adenine and potassium oxinate. Biochemical analysis and hematoxylin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…We further explored the mechanism of resveratrol on XO in human HepG2 cells and found that FFA treatment increased uric acid levels in the supernatants and intracellular XO activity, and resveratrol (10 μmol/L) significantly decreased the uric acid and activity of XO. Taken together, these results suggest that the uric acid-lowering effect of resveratrol can be attributed to a certain extent to decreased uric acid production mediated by decreasing XO activity, consistent with the literature [ 44 , 53 ]. Although the dosage of resveratrol in cell experiment (10 μmol/L) was higher than the physiological concentration reported [ 54 ], it is at a low dose level in previous in vitro studies [ 55 , 56 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We further explored the mechanism of resveratrol on XO in human HepG2 cells and found that FFA treatment increased uric acid levels in the supernatants and intracellular XO activity, and resveratrol (10 μmol/L) significantly decreased the uric acid and activity of XO. Taken together, these results suggest that the uric acid-lowering effect of resveratrol can be attributed to a certain extent to decreased uric acid production mediated by decreasing XO activity, consistent with the literature [ 44 , 53 ]. Although the dosage of resveratrol in cell experiment (10 μmol/L) was higher than the physiological concentration reported [ 54 ], it is at a low dose level in previous in vitro studies [ 55 , 56 ].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the effect of resveratrol on hyperuricemia, animal studies showed that resveratrol reduced serum uric acid concentration by inhibiting XO to reduce uric acid production [ 44 ] and regulating organic ion transporters to increase uric acid excretion [ 45 , 46 ], which are inconsistent with the results of clinical studies. It has been reported that resveratrol dimers significantly reduced uric acid levels in healthy subjects [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2021 ), drug-induced kidney injury (DKI) (Xiao et al. 2021 ) and sepsis-associated acute kidney injury (SA-AKI) (Wang et al. 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the same context, the renoprotective effect of resveratrol appears via activation of the SIRT1/FOXO1 pathway and enhances mitochondrial biogenesis with Mn-SOD. Moreover, it prevents glomerulosclerosis, and attenuated renotoxicity-induced by lipopolysaccharides may be via reduced SIRT3 activity (33)(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%